2015
DOI: 10.1111/tbed.12375
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Surveillance in the Lombardy Region, Northern Italy

Abstract: In 2013, the circulation of West Nile virus (WNV) was detected in the Lombardy region and the following year a surveillance programme was activated with the aim of early identification of the viral distribution in mosquitoes and wild birds. A total of 50 959 Culex spp. mosquitoes grouped in six hundred and forty-seven pools as well as 1400 birds were screened by RT-PCR for the presence of West Nile virus leading to the identification of the viral genome in 32 mosquito pools and 13 wild birds. The surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Moreover, all squirrels that showed VNT‐positive results for either WNV, USUV or TBEV were trapped in Piedmont. In this respect, our results contrast with the higher circulation of WNV and USUV detected in both humans and competent vectors in Lombardy region during the study period (Calzolari et al., ; CESME, ; Chiari et al., ; Mancini et al., ; Rizzo et al., ). The regional difference in seroprevalence observed in our study is likely related to habitat differences between the distribution range of grey squirrels in the two regions.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Moreover, all squirrels that showed VNT‐positive results for either WNV, USUV or TBEV were trapped in Piedmont. In this respect, our results contrast with the higher circulation of WNV and USUV detected in both humans and competent vectors in Lombardy region during the study period (Calzolari et al., ; CESME, ; Chiari et al., ; Mancini et al., ; Rizzo et al., ). The regional difference in seroprevalence observed in our study is likely related to habitat differences between the distribution range of grey squirrels in the two regions.…”
Section: Resultscontrasting
confidence: 95%
“…Conversely, most sampling sites in Lombardy were larger woods with a drier climate, which are less favourable habitats for the development of mosquito vectors. Indeed, most of flavivirus outbreaks reported in Lombardy region were located further to the south than our study areas and outside of grey squirrels’ introduction range (e.g., Calzolari et al., ; Chiari et al., ; Rovida et al., ). Seropositivity to flaviviruses significantly varied also across years (χ22 = 6.7, p = .04), with a higher seroprevalence in squirrels sampled in 2011 (29.0%; 9/31), compared to 2012 (6.9%; 5/72) and 2013 (5.4%; 3/55).…”
Section: Resultsmentioning
confidence: 61%
“…Friuli Venezia Giulia, Emilia Romagna, Lombardy, Piedmont, Veneto, operate an enhanced surveillance system based on a network of fixed mosquito traps (in grids from 10 to 20 km) and on the collection of residential wild birds, mainly Corvidae. Timely data on viral circulation triggers preventive measures to avoid the virus transmission via blood, tissue and organ donations [ 15 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes of the Culex pipiens complex and Culex torrentium Martini (Diptera: Culicidae), are widespread and abundant in Central Europe (Rudolf et al ., ; Hesson et al ., ) and have been shown to transmit Sindbis virus in Sweden, West Nile virus (WNV) in Italy and Usutu virus in Austria and Germany (Lundstrom et al ., , ; Jost et al ., ; Chiari et al ., ; Hesson et al ., ; Leggewie et al ., ). To date, contradictory observations have been reported concerning the relationship between Wolbachia and Culex mosquitoes.…”
mentioning
confidence: 98%
“…What is more, knowledge about the Wolbachia infection status could contribute to the assessment of the vector potential of a given mosquito species. As mentioned above, members of the Culex complex, namely C. pipiens biotype pipiens , C. pipiens biotype molestus and C. torrentium , are present in Germany (Rudolf et al ., ) and are susceptible to WNV as well as Sindbis virus infection (Lundstrom et al ., , ; Chiari et al ., ; Hesson et al ., ; Leggewie et al ., ). Earlier studies in which the presence of Wolbachia was determined showed that 80–100% of C. pipiens biotypes were infected (Rasgon & Scott, ; Duron et al ., ; Fedorova & Shaikevich, ; Khrabrova et al ., ; Zele et al ., ; Raharimalala et al ., ), but data on Wolbachia infection rates in C. torrentium are inconclusive.…”
mentioning
confidence: 98%